(3SjQI QShd Gddg Udi Gddg Ydjg hSdes - (3YHO Gdedc Hf gTGe Hf CjhH GdMejQj GdeYGaQj, CHh eMeO, LeGd GdOjf,J (B213 (3g` s
(3ChdgG (B:s
(3Yf CHj eMeO YHO Gdedc Hf gTGe GdHUQi cJGH SjQI QShd Gddg Udi Gddg Ydjg hSde eMeO Hf YHO Gddg Hf YHO GdeWdH s
(3BNQgG (B:s
(3bGd GHf gTGe (B: (3YLR GdHjJ GdChd Yf ZjQ GHf ESMGb gfGJe LejY GdOjhGf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B166 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B192s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B206 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B132 s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(1687) s
Keywords: (3GdJGQjNs